Plant Stress Physiology - Hossain, Akbar (IntechOpen, 2021)
Due to the changing climate, food security for the increasing population has raised a great threat globally. Therefore, it is imperative to find alternate solutions for enhancing agricultural sustainability through plant stress physiology. The concept of plant stress physiology has been well-established over the past 60 years due to the increasing trends of environmental stress. Researchers have found that crop stress physiology has an association with two main areas, one is concerned with agronomy, the other concerned with plant breeding. The contents of the current book emphasize the integration of both breeding and agronomy strategies to ensure agricultural productivity and environmental safety under changing climate.